Assessing Public Financing for Nutrition in Bhutan, India, Nepal, and Sri Lanka - World Bank (World Bank, Washington, DC, 2021)
Overall nutrition-specific expenditure in Bhutan, India, Nepal, and Sri Lanka remains low, although substantial variation exists among these countries. Given the high rates of malnutrition in these countries, it is important to identify more fiscal space for nutrition, and to prioritize funding of proven, high-impact interventions. The share of spending on nutrition-specific versus nutrition-sensitive interventions should be carefully balanced in relation to the expected impact of the interventions being funded. The cause of underutilization of nutrition-related allocations should be analyzed to improve utilization or free up funds for interventions that are high-impact and well-executed. There are substantial limitations to tracking nutrition expenditures within the current budget allocation records. Standardized systems of data collection are recommended for all countries in the region and beyond. Standardized global guidance is needed for defining nutrition-sensitive and nutrition-specific interventions to enhance comparability between studies in different countries.